PENATALAKSANAAN DAN PENCEGAHAN REAKSI HIPERSENSITIVITAS AKUT AKIBAT MEDIA KONTRAS - Andari Kluniari, Ni Made Nova; Suardamana, I Ketut (Ganesha Medicina, 2023)
The used of iodinated contrast media have increased in recent years. It has been estimated that in the United States alone, 15 million procedures a year contrast media. Approximately 2-3 % patient do pyelogram and myelogram retrograde occurred anaphylactoid reaction. The reaction event during procedure using iodinated contrast media could be fatal. The activated mast cell was not mediated by IgE. Although the use of Low Osmolarity iodinated contrast media could lower the risk of allergic reaction, it was still possible to occur anaphylactoid reaction during the procedure. Here we reported allergic event after using contrast media during PCI procedure. The symptom was relieved with steroid and antihistamin therapy. In this report we focus to discuss the management of preventing allergic reaction and the therapy if the allergic reaction occur.